Growth and Development of Rhyzopertha dominica Fabricius (Coleoptera: Bostrichidae) on White, Red and Black Rice - Fajarwati, Dewi; Astuti, Ludji Pantja; Himawan, Toto (Graduate School, Universitas Brawijaya, 2019)
Rhyzopertha dominica is a polyphagous stored pest to many grains including rice. R. dominica can easily spread from one place to another to infest stored products. The aim of this research was to know the influence of three grains types with different weight to R. dominica growth, development, net reproduction rate and gross reproduction rate on red, black and white rice. The research was conducted in Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, University of Brawijaya Malang. The research result showed that there was an interaction among three grains types with different weight to the number of R. dominica larval, pupal, and newly adult emerged, while the number of eggs, weight of newly adult emerged, the reduction percentage of grain and phase of the egg, larval, pupal and the life cycle period of R. dominica were affected by different grains types factor. The R0value showed that on the next generation, number of female was increase 1.25 times from the previous generation on white rice, while on red and black rice the population was increase up to 2.63 and 2.49 times from the previous generation.Keywords: Growth and Development, Reproduction Rate, Rice, Rhyzopertha dominica.